THE INFLUENCE OF PRODUCT DIVERSITY AND STORE LOCATION ON PURCHASE DECISIONS OF CONSUMERS AT VIERA OLEH-OLEH PEKANBARU - Rahmadani, Cindy Dwi; Othman, Lie (Journal of Management Small and Medium Enterprises (SMEs), 2025)
Purchasing decisions play a crucial role in the marketing concept. This is the background to this research. Product diversity and good store locations are some of the incentives for someone to make a purchase. This is what the Viera Pekanbaru Souvenir Shop implements. This research aims to determine the influence of product diversity and shop location on purchasing decisions at the Viera Pekanbaru Souvenir Shop. The research method employed in this study is a descriptive approach with quantitative methods. Research data sources come from primary data. The number of samples in this research was 100 people, with the sampling technique using purposive sampling. The analytical method for this research is multiple linear regression analysis and uses validity and reliability tests. The results obtained are that product diversity has a positive and significant effect on purchasing decisions, store location has a positive and significant effect on purchasing decisions, and product diversity and store location simultaneously influence purchasing decisions at the Viera Pekanbaru Souvenir Shop. Keywords: Product Diversity; Store Location; Purchase Decision